An electrocatalyst and a method for preparing the same
Patent Information
- Application Number
- CN202510572800.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-04-30
AI Technical Summary
目前,电催化剂中贵金属的载量较高,导致的贵金属的利用率低、使用成本较高
[0007]本发明提供了一种电催化剂的制备方法,采用三电极系统,对工作电极进行活化,得到活化后的导电碳材料,再利用活化后的导电碳材料作为还原剂,对贵金属盐溶液中的贵金属离子进行还原,本发明通过控制活化过程中的电位或电流,能够保证本发明的电催化剂具有较低的贵金属的载量以及较高的催化性能,能有效解决因电催化剂中贵金属的载量较高导致的贵金属利用率低、膜电极和电堆成本增加问题和因贵金属的载量过低导致的电催化剂活性和耐久性大幅度衰减问题,可见,本发明的制备方法对于扩大氢气作为新能源的应用范围具有重要意义;此外,本发明采用的方法具有工艺简单、易于操作、过程可控、成本低廉的优点。
Smart Images

Figure CN120505664B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of water electrolysis and fuel cell technology, and specifically to an electrocatalyst and its preparation method. Background Technology
[0002] Hydrogen energy, as a key component of the national energy strategy, has garnered widespread attention. Hydrogen production through water electrolysis, a primary source of "green hydrogen," has attracted significant interest and active investment from various companies. Hydrogen fuel cells, as carriers of hydrogen energy, are widely used in vehicle transportation, shipping, and grid energy storage. Meanwhile, proton exchange membrane water electrolysis (PEM) remains in the laboratory research stage due to its high cost and has not yet achieved large-scale commercial operation. Furthermore, there is a growing focus on cost reduction for hydrogen fuel cell systems, particularly in the area of electrocatalyst materials, which account for approximately 13% of the total vehicle cost. Cost reduction and efficiency improvement strategies for electrocatalyst materials are a hot research topic and a future development trend for electrocatalyst companies. Achieving cost reduction and efficiency improvement for electrocatalyst materials has become a key technology for driving cost reduction and rapid popularization of fuel cell stacks and systems. Currently, electrocatalysts have high precious metal loadings, resulting in low utilization rates and high operating costs.
[0003] Therefore, there is an urgent need to develop an electrocatalyst with a low noble metal loading suitable for hydrogen fuel cells. Summary of the Invention
[0004] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, the present invention provides an electrocatalyst and a method for preparing the same, wherein the electrocatalyst prepared by the method of the present invention has a low noble metal loading and high catalytic performance.
[0005] The first aspect of this invention provides a method for preparing an electrocatalyst, comprising the following steps:
[0006] Using conductive carbon material as the working electrode, the working electrode, counter electrode, and reference electrode are fixed in an electrolyte. The working electrode is activated by maintaining its potential at -1 to -4V using a constant potential method or by applying a current of 1 to 5mA using a constant current method to obtain the activated conductive carbon material. The activated conductive carbon material is then reacted with a noble metal salt solution to obtain an electrocatalyst. The noble metal salt solution includes a platinum salt solution and / or a palladium salt solution.
[0007] This invention provides a method for preparing an electrocatalyst. A three-electrode system is used to activate the working electrode, yielding activated conductive carbon material. This activated conductive carbon material is then used as a reducing agent to reduce noble metal ions in a noble metal salt solution. By controlling the potential or current during the activation process, this invention ensures that the electrocatalyst has a low noble metal loading and high catalytic performance. It effectively solves the problems of low noble metal utilization and increased costs of membrane electrodes and stacks due to high noble metal loading, and the significant decline in electrocatalyst activity and durability due to low noble metal loading. Therefore, this preparation method is of great significance for expanding the application scope of hydrogen as a new energy source. Furthermore, the method employed in this invention has the advantages of simple process, ease of operation, process controllability, and low cost.
[0008] In some embodiments of the present invention, the potential of the working electrode is maintained at -2 to -2.4V in a constant potential manner. This can further improve the catalytic performance of the electrocatalyst.
[0009] In some embodiments of the present invention, the activation time is 20 seconds to 3 minutes. Activation can increase the reactivity of the electrode, increase the number of active sites on the surface of the conductive carbon material, and allow cations in the electrolyte to be mounted on the surface of the conductive carbon material, thereby improving the electrochemical performance of the electrode. The present invention, by controlling the activation time, enables the electrode to reach a stable electrochemical state, which is beneficial for the conductive carbon material to carry out subsequent reactions.
[0010] In some embodiments of the present invention, the reaction time is ≥5s. By controlling the reaction time, the size and loading of noble metal particles in the electrocatalyst can be controlled. Furthermore, controlling the reaction time can also ensure that the noble metal is uniformly dispersed in the conductive carbon material, avoiding agglomeration, thereby improving the electrocatalytic performance of the electrocatalyst.
[0011] In some embodiments of the present invention, the conductive carbon material includes one or more of graphite, carbon nanotubes, carbon black, biochar, and activated carbon. The above-mentioned conductive carbon materials have good conductivity, enabling rapid charge transfer and improving the efficiency of the activation process. Furthermore, the structure of the above-mentioned conductive carbon materials is stable, which can improve the stability of the electrocatalyst.
[0012] In some embodiments of the present invention, the electrolyte comprises an organic electrolyte salt.
[0013] In some embodiments of the present invention, the organic electrolyte salt includes organic lithium salts and / or organic ammonium salts.
[0014] In some embodiments of the present invention, the organic lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium bis(oxalate borate), lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, and lithium tri(trifluoromethanesulfonyl)methyl. The above-mentioned organic lithium salts have high ionic conductivity and can form good ion transport channels in the electrolyte, which is beneficial for loading lithium ions into the above-mentioned conductive carbon material.
[0015] In some embodiments of the present invention, the organic ammonium salt includes one or more of the following: ammonium tetrafluoroborate, ammonium hexafluorophosphate, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, tetraethylammonium tetrafluoroborate, tetraethylammonium hexafluorophosphate, bis(trifluoromethanesulfonyl)imide tetraethylammonium, bis(fluorosulfonyl)imide tetraethylammonium, methylammonium tetrafluoroborate, and methylammonium hexafluorophosphate. The above-mentioned organic ammonium salts have high ionic conductivity and can form good ion transport channels in the electrolyte, which is beneficial for loading ammonium ions into the above-mentioned conductive carbon material.
[0016] In some embodiments of the present invention, the concentration of the organic electrolyte salt is 0.01–0.1 mol / L, based on the volume of the electrolyte. An appropriate electrolyte salt concentration ensures good ionic conductivity of the electrolyte, thereby improving the rate and efficiency of the electrode reaction. Furthermore, excessively high electrolyte salt concentrations can lead to concentration polarization, i.e., a large difference in ion concentration between the electrode surface and the solution, thus affecting the uniformity of the electrode reaction. By controlling the concentration, concentration polarization can be reduced, ensuring the uniformity of the activation process.
[0017] In some embodiments of the present invention, the concentration of the noble metal salt is 1 mmol / L to 1 mol / L, based on the volume of the noble metal salt solution. The concentration of the noble metal salt affects the deposition rate of metal ions. The present invention, by adjusting the concentration, forms more uniform and smaller particles in the conductive carbon material, thereby improving the electrocatalytic performance of the electrocatalyst. Furthermore, by controlling the concentration of the noble metal salt, the bonding strength between the noble metal particles and the conductive carbon material can be optimized, reducing the shedding of noble metal particles during use and improving the stability of the electrocatalyst.
[0018] A second aspect of the present invention provides an electrocatalyst prepared by the above-described method.
[0019] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0020] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:
[0021] Figure 1 A flowchart illustrating a method for preparing an electrocatalyst according to an embodiment of the present invention is shown;
[0022] Figure 2 The polarization activation curves of G1, G2, and G3 in Embodiment 1 of the present invention are shown;
[0023] Figure 3 The X-ray diffraction pattern of the Pt / G electrocatalyst of Example 1 of the present invention is shown;
[0024] Figure 4 The image shows the scanning electron microscope energy dispersive spectroscopy (EDS) analysis of the Pt / G electrocatalyst of Example 1 of the present invention;
[0025] Figure 5 An electron microscope image of the Pt / G electrocatalyst of Example 1 of the present invention is shown;
[0026] Figure 6 The hydrogen evolution reaction curves of the electrocatalysts (Pd / G, Pt / G, PtPd / G) of Example 1 of the present invention and the commercial electrocatalyst (Pt / C / G) are shown.
[0027] Figure 7 The hydrogen evolution reaction curve of the electrocatalyst of Example 2 of the present invention is shown;
[0028] Figure 8 The hydrogen evolution reaction curve of the electrocatalyst of Example 3 of the present invention is shown;
[0029] Figure 9 The hydrogen evolution reaction curve of the electrocatalyst of Example 4 of the present invention is shown;
[0030] Figure 10 The hydrogen evolution reaction curves of the electrocatalysts in Examples 5 and 6 of this invention are shown;
[0031] Figure 11 The hydrogen evolution reaction curves of the electrocatalysts in Examples 7 and 8 of this invention are shown;
[0032] Figure 12 The hydrogen evolution reaction curve of the Pt / G electrocatalyst of Example 1 of the present invention is shown;
[0033] Figure 13 The oxygen reduction reaction curve of the Pt / G electrocatalyst of Example 1 of the present invention is shown. Detailed Implementation
[0034] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0035] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0036] Currently, there is much discussion about cost reduction in hydrogen fuel cell systems. In particular, cost reduction and efficiency improvement strategies for electrocatalyst materials, which account for approximately 13% of the total vehicle cost, are a hot research topic and a future development trend for catalyst companies. Achieving cost reduction and efficiency improvement for electrocatalyst materials has become a key technology for driving cost reduction and rapid popularization of fuel cell stacks and systems. Currently, electrocatalysts have a high loading of precious metals, resulting in low utilization rates and high operating costs.
[0037] Therefore, this invention provides a method for preparing an electrocatalyst. A three-electrode system is used to activate the working electrode, obtaining activated conductive carbon material. This activated conductive carbon material is then used as a reducing agent to reduce noble metal ions in a noble metal salt solution. The method of this invention has the advantages of simple process, ease of operation, process controllability, and low cost. Furthermore, by controlling the potential or current during the activation process, the electrocatalyst of this invention can be guaranteed to have a low noble metal loading and high catalytic performance. This effectively solves the problems of low noble metal utilization and increased costs of membrane electrodes and stacks due to high noble metal loading in the electrocatalyst, and the significant decline in electrocatalyst activity and durability due to excessively low noble metal loading. Therefore, the preparation method of this invention is of great significance for expanding the application scope of hydrogen as a new energy source.
[0038] The first aspect of this invention provides a method for preparing an electrocatalyst, comprising the following steps:
[0039] S100. Using conductive carbon material as the working electrode, the working electrode, counter electrode, and reference electrode are fixed in the electrolyte. The potential of the working electrode is maintained at -1 to -4V in a constant potential manner or a current of 1 to 5mA is applied in a constant current manner to activate it, thereby obtaining the activated conductive carbon material.
[0040] In some embodiments of the present invention, the activation time is 20 s to 3 min. As examples, the activation time can be 20 s, 30 s, 40 s, 50 s, 60 s, 70 s, 80 s, 90 s, 100 s, 110 s, 2 min, 2.5 min, or 3 min. Activation can increase the reactivity of the electrode, increase the number of active sites on the surface of the conductive carbon material, and allow cations in the electrolyte to be mounted on the surface of the conductive carbon material, thereby improving the electrochemical performance of the electrode. The present invention, by controlling the activation time, enables the electrode to reach a stable electrochemical state, which is beneficial for the subsequent reactions of the conductive carbon material.
[0041] In some preferred embodiments of the present invention, the activation time is 20s to 30s.
[0042] This invention does not have special requirements for the conductive carbon material, as long as it does not react with the electrolyte. In some embodiments of this invention, the conductive carbon material includes one or more of graphite, carbon nanotubes, carbon black, biochar, and activated carbon. The above-mentioned conductive carbon materials have good conductivity, enabling rapid charge transfer and improving the efficiency of the activation process. Furthermore, the structure of these conductive carbon materials is stable, which can improve the stability of the electrocatalyst.
[0043] In some embodiments of the present invention, the counter electrode comprises an inert material, specifically including one or more of platinum and carbon electrodes.
[0044] In some embodiments of the present invention, the present invention does not have special requirements for the reference electrode, and commercially available reference electrodes can be used, such as saturated mercurous sulfate / mercuric sulfate, saturated calomel electrode, or Ag / AgCl.
[0045] In some embodiments of the present invention, the electrolyte comprises an organic electrolyte salt; the organic electrolyte salt comprises an organic lithium salt and / or an organic ammonium salt.
[0046] In some embodiments of the present invention, the organic lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium bis(oxalate borate), lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, and lithium tri(trifluoromethanesulfonyl)methyl. The above-mentioned organic lithium salts have high ionic conductivity and can form good ion transport channels in the electrolyte, which is beneficial for loading lithium ions into the above-mentioned conductive carbon material.
[0047] In some embodiments of the present invention, the organic ammonium salt includes one or more of the following: ammonium tetrafluoroborate, ammonium hexafluorophosphate, bis(trifluoromethanesulfonyl)imide, bis(fluorosulfonyl)imide, tetraethylammonium tetrafluoroborate, tetraethylammonium hexafluorophosphate, bis(trifluoromethanesulfonyl)imide tetraethylammonium, bis(fluorosulfonyl)imide tetraethylammonium, methylammonium tetrafluoroborate, and methylammonium hexafluorophosphate. The above-mentioned organic ammonium salts have high ionic conductivity and can form good ion transport channels in the electrolyte, which is beneficial for loading ammonium ions into the above-mentioned conductive carbon material.
[0048] In some embodiments of the present invention, the organic electrolyte salt further includes a solvent.
[0049] In some embodiments of the present invention, the solvent includes one or more of acetonitrile, propionitrile, N,N-dimethylformamide, ethylene carbonate, propylene carbonate, dimethyl carbonate, methyl ethyl carbonate, sulfolane, dimethyl sulfone, trimethyl phosphate, and triethyl phosphate.
[0050] In some embodiments of the present invention, the concentration of the organic electrolyte salt is 0.01–0.1 mol / L based on the volume of the electrolyte. As an example, the concentration of the organic electrolyte salt can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1 mol / L based on the volume of the electrolyte. An appropriate electrolyte salt concentration ensures good ionic conductivity of the electrolyte, thereby improving the rate and efficiency of the electrode reaction. Furthermore, excessively high electrolyte salt concentrations can lead to concentration polarization, i.e., a large difference in ion concentration between the electrode surface and the solution, thus affecting the uniformity of the electrode reaction. By controlling the concentration, concentration polarization can be reduced, ensuring the uniformity of the activation process.
[0051] In some embodiments of the present invention, as an example, the potential of the working electrode can be maintained in a constant potential manner as -1, -1.5, -2, -2.4, -2.5, -3, -3.5, or -4V.
[0052] In some embodiments of the present invention, the potential of the working electrode is maintained at -2 to -2.4V in a constant potential manner. This can further improve the catalytic performance of the electrocatalyst.
[0053] In some embodiments of the present invention, as an example, currents of 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, and 5 mA are applied in a constant current manner.
[0054] In some embodiments of the present invention, the conductive carbon material is cleaned before being used as the working electrode; further, the conductive carbon material is ultrasonically cleaned; even further, the ultrasonic cleaning frequency is 40-60 kHz and the time is 15-30 min; even further, the cleaned conductive carbon material is dried. Cleaning can effectively remove impurities, dust, oil, and other contaminants from the surface of the conductive carbon material, reducing the negative impact on subsequent activation.
[0055] In some embodiments of the present invention, after obtaining the activated conductive carbon material, the activated conductive carbon material is allowed to stand before the reaction is carried out; further, the standing conductive carbon material is cleaned; water or organic solvent can be used for cleaning.
[0056] S200. The activated conductive carbon material is reacted with a noble metal salt solution to obtain an electrocatalyst; the noble metal salt solution includes a platinum salt solution and / or a palladium salt solution. Platinum and palladium have excellent catalytic activity and can significantly improve the rate and efficiency of electrochemical reactions. Using a noble metal salt solution as a precursor can form highly dispersed noble metal ion particles, thereby reacting with the activated conductive carbon material.
[0057] In some embodiments of the present invention, reacting the activated conductive carbon material with the noble metal salt solution specifically includes: placing the activated conductive carbon material in the noble metal salt solution, reacting, and removing the reacted conductive carbon material from the system.
[0058] In some embodiments of the present invention, the solvent of the noble metal salt solution is a liquid capable of dissolving the noble metal salt, which may include one or more of water, inorganic acid, inorganic base, and alcohol compounds.
[0059] In some embodiments of the present invention, the platinum salt in the platinum salt solution includes one or more of PtCl2, PtCl4, Pt(NO3)2, Pt(NO3)4, PtSO4, Pt(SO4)2, Pt(CH3COO)2, Pt(CN)2, Pt(CN)4, Pt(C2O4)2, PtCO3, and K2PtCl6. The above platinum salts exhibit high catalytic activity and stability, making them suitable for a variety of electrocatalytic reactions.
[0060] In some embodiments of the present invention, the palladium salt in the palladium salt solution includes one or more of PdCl2, PdBr2, Pd(NO3)2, Pd(CH3COO)2, (NH4)2PdCl6, Na2PdCl4, PdI2, Pd(NH3)2Cl2, and Na2Pd(NO3)4. The above palladium salts exhibit high catalytic activity and stability, making them suitable for a variety of electrocatalytic reactions.
[0061] In some embodiments of the present invention, the concentration of the noble metal salt is 1 mmol / L to 1 mol / L, based on the volume of the noble metal salt solution. As an example, the concentration of the noble metal salt can be 1 mmol / L, 10 mmol / L, 50 mmol / L, 100 mmol / L, 200 mmol / L, 300 mmol / L, 400 mmol / L, 500 mmol / L, 600 mmol / L, 700 mmol / L, 800 mmol / L, 900 mmol / L, or 1 mol / L, based on the volume of the noble metal salt solution. The concentration of the noble metal salt affects the deposition rate of metal ions. The present invention, by adjusting the concentration, forms more uniform and smaller particles in the conductive carbon material, thereby improving the electrocatalytic performance of the electrocatalyst. Furthermore, by controlling the concentration of the noble metal salt, the bonding strength between the noble metal particles and the conductive carbon material can be optimized, reducing the shedding of noble metal particles during use and improving the stability of the electrocatalyst.
[0062] In some embodiments of the present invention, the concentration of the platinum salt is 1 mmol / L to 1 mol / L, based on the volume of the platinum salt solution. As an example, the concentration of the platinum salt can be 1 mmol / L, 10 mmol / L, 50 mmol / L, 100 mmol / L, 200 mmol / L, 300 mmol / L, 400 mmol / L, 500 mmol / L, 600 mmol / L, 700 mmol / L, 800 mmol / L, 900 mmol / L, or 1 mol / L, based on the volume of the platinum salt solution. The concentration of the platinum salt affects the deposition rate of metal ions. The present invention, by adjusting the concentration, forms more uniform and smaller particles in the conductive carbon material, thereby improving the electrocatalytic performance of the electrocatalyst. Furthermore, by controlling the concentration of the platinum salt, the bonding strength between the platinum particles and the conductive carbon material can be optimized, reducing platinum particle detachment during use and improving the stability of the electrocatalyst.
[0063] In some embodiments of the present invention, the concentration of the palladium salt is 1 mmol / L to 1 mol / L based on the volume of the palladium salt solution. As an example, the concentration of the palladium salt can be 1 mmol / L, 10 mmol / L, 50 mmol / L, 100 mmol / L, 200 mmol / L, 300 mmol / L, 400 mmol / L, 500 mmol / L, 600 mmol / L, 700 mmol / L, 800 mmol / L, 900 mmol / L, or 1 mol / L, based on the volume of the palladium salt solution. The concentration of the palladium salt affects the deposition rate of metal ions. The present invention, by adjusting the concentration, forms more uniform and smaller particles in the conductive carbon material, thereby improving the electrocatalytic performance of the electrocatalyst. Furthermore, by controlling the concentration of the palladium salt, the bonding strength between the palladium particles and the conductive carbon material can be optimized, reducing the shedding of palladium particles during use and improving the stability of the electrocatalyst.
[0064] In some embodiments of the present invention, the reaction time is ≥5s, and more specifically, the reaction time is 5s to 5min. As examples, the reaction time can be 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s, 15s, 16s, 17s, 18s, 19s, 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s, 100s, 110s, 2min, 3min, 4min, or 5min. By controlling the reaction time, the size and loading of noble metal particles in the electrocatalyst can be controlled. Furthermore, controlling the reaction time can ensure that the noble metal is uniformly dispersed in the conductive carbon material, avoiding agglomeration, thereby improving the electrocatalytic performance of the electrocatalyst.
[0065] In some preferred embodiments of the present invention, the reaction time is 30s to 1min.
[0066] In some embodiments of the present invention, the method for preparing the electrocatalyst, such as Figure 1 As shown, the process includes the following steps, wherein steps 3) to 4) are carrier activation steps, and steps 5) to 7) are metal reduction steps:
[0067] 1) Conductive carbon material was used as a carrier material and cleaned. Electrolytes, platinum salt solutions, and palladium salt solutions were prepared. The graphite rods were then ultrasonically cleaned, which effectively removed impurities, dust, oil, and other contaminants from the surface of the graphite rods.
[0068] 2) Use the carrier material as the working electrode, and immerse the working electrode, counter electrode, and reference electrode in the electrolyte;
[0069] 3) Apply activation drive to maintain the working electrode potential at -1 to -4V in a constant potential manner or apply a current of 1 to 5mA in a constant current manner (chronoamperometry) (cyclic voltammetry);
[0070] 4) After activation for 20 seconds to 3 minutes, rinse the activated carrier material;
[0071] 5) The activated carrier is immersed in a noble metal salt solution to carry out the reaction;
[0072] 6) Immerse the activated carrier in the noble metal salt solution and let the carrier material stand for more than 5 seconds;
[0073] 7) After the reaction is complete, remove the support material loaded with platinum and / or palladium from the electrolyte and rinse it.
[0074] 8) Obtain an electrocatalyst;
[0075] 9) Perform relevant tests on the prepared electrocatalyst, including electrochemical performance testing.
[0076] A second aspect of the present invention provides an electrocatalyst prepared by the above-described method.
[0077] The electrocatalyst of this invention has good structural stability and high catalytic activity. When this structurally stable and catalytically effective material is used for electrocatalytic hydrogen evolution, the electrocatalytic reaction can be triggered at a lower driving current, thereby reducing hydrogen evolution energy consumption, obtaining higher hydrogen evolution efficiency and higher hydrogen production, and significantly improving the hydrogen evolution effect.
[0078] In some embodiments of the present invention, the mass content of platinum and / or palladium is <1% based on the mass of the electrocatalyst.
[0079] In some embodiments of the present invention, the mass content of platinum and / or palladium is 0.1%-1% based on the mass of the electrocatalyst. As an example, the mass content of platinum and / or palladium may be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1% based on the mass of the electrocatalyst.
[0080] The present disclosure will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be construed as limiting the scope of the disclosure. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially. The commercial Pt / C used in the embodiments and comparative examples of this invention was purchased from Alfaisa (China) Chemical Co., Ltd., product number 047381; the graphite rod carrier was purchased from Alfaisa (China) Chemical Co., Ltd., product number 040765.
[0081] Example 1
[0082] The electrocatalyst of this embodiment is prepared by the following steps:
[0083] 1) Preparation of graphite rods: Place the graphite rods in an ultrasonic cleaning device containing ethanol, turn on the device, set the ultrasonic power to 300W, and the time to 15 minutes to perform ultrasonic cleaning on the graphite rods. Ultrasonic cleaning can effectively remove impurities, dust, oil, and other contaminants from the surface of the graphite rods. After ultrasonic cleaning, dry the graphite rods at 80℃ for 0.5 hours to ensure that the ethanol on the surface of the graphite rods completely evaporates and leaves no residual liquid. After drying, properly store the graphite rods in a clean and dry container for use as a carrier in subsequent experiments.
[0084] 2) Solvent preparation: Polarization activation electrolyte: 0.1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) acetonitrile solution; Pt metal salt reduction solution A: 0.1M potassium chloroplatinate (K2PtCl6) aqueous solution; Pd metal salt reduction solution B: 0.1M palladium nitrate (Pd(NO3)2) aqueous solution; Pt+Pd metal salt reduction solution C: 0.05M potassium chloroplatinate aqueous solution + 0.05M palladium nitrate aqueous solution.
[0085] 3) Support Activation: Graphite rods were used as the working electrode and counter electrode, respectively, with Ag / AgCl as the reference electrode. In a 0.1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) solution, the working electrode, counter electrode, and reference electrode were connected to an electrochemical workstation. Using electrochemical cathode activation technology, -2.4V was applied to activate the graphite rod at the working electrode for 30 seconds, resulting in three activated graphite rod electrodes, designated G1, G2, and G3, respectively. The polarization activation curves are shown below. Figure 2 As shown, by Figure 2 It can be seen that the polarization curves have the same trend, that is, as time increases, the current gradually increases until it tends to be horizontal, indicating that the polarization results of the three graphite rods are almost the same.
[0086] 4) Metal reduction: After activation, the three graphite rods are quickly rinsed with anhydrous ethanol and then placed in reducing solutions A, B, and C respectively for 30 seconds. After reduction, they are taken out, quickly rinsed with water, and dried to obtain electrocatalysts with ultra-low Pt and / or Pd loading, namely Pd / G electrocatalyst, Pt / G electrocatalyst and PtPd / G electrocatalyst.
[0087] Example 2
[0088] The electrocatalyst of this embodiment differs from that of Example 1 in that: in step 2), the preparation steps of reduction solution B and reduction solution C are omitted, and in step 3), a graphite rod with a -3V activation working electrode is applied for 30s to obtain the electrocatalyst.
[0089] The remaining steps are performed in accordance with Example 1.
[0090] Example 3
[0091] The electrocatalyst of this embodiment differs from that of Example 1 in that: in step 2), the preparation steps of reduction solution B and reduction solution C are omitted, and in step 3), a graphite rod with an activation working electrode of -3.2V is applied for 30s to obtain the electrocatalyst.
[0092] The remaining steps are performed in accordance with Example 1.
[0093] Example 4
[0094] The electrocatalyst of this embodiment differs from that of Example 1 in that: in step 2), the preparation steps of reduction solution B and reduction solution C are omitted, and in step 3), the graphite rod of the working electrode is activated by applying -1.5V for 30s to obtain the electrocatalyst.
[0095] The remaining steps are performed in accordance with Example 1.
[0096] Example 5
[0097] The electrocatalyst of this embodiment differs from that of Example 1 in that: in step 2), the preparation steps of reduction solution B and reduction solution C are omitted, and in step 3), the graphite rod of the working electrode is activated by applying -2.4V for 1 minute to obtain the electrocatalyst.
[0098] The remaining steps are performed in accordance with Example 1.
[0099] Example 6
[0100] The electrocatalyst of this embodiment differs from that of Example 1 in that: in step 2), the preparation steps of reduction solution B and reduction solution C are omitted, and in step 3), the graphite rod of the working electrode is activated by applying -2.4V for 3 minutes to obtain the electrocatalyst.
[0101] The remaining steps are performed in accordance with Example 1.
[0102] Example 7
[0103] The electrocatalyst of this embodiment differs from that of Example 1 in that: in step 2), the preparation steps of reduction solution B and reduction solution C are omitted, and in step 4), the reduction time is 5s to obtain the electrocatalyst.
[0104] The remaining steps are performed in accordance with Example 1.
[0105] Example 8
[0106] The electrocatalyst of this embodiment differs from that of Example 1 in that: in step 2), the preparation steps of reduction solution B and reduction solution C are omitted, and in step 4), the reduction time is 5 minutes to obtain the electrocatalyst.
[0107] The remaining steps are performed in accordance with Example 1.
[0108] Comparative Example 1
[0109] The electrocatalyst of this comparative example differs from that of Example 1 in that: in step 2), the preparation steps of reduction solution B and reduction solution C are omitted, and in step 3), a graphite rod with an activation working electrode of -2.4V is applied for 18s to obtain the electrocatalyst.
[0110] The remaining steps are performed in accordance with Example 1.
[0111] Test case
[0112] 1. X-ray diffraction (XRD) test
[0113] X-ray diffraction testing was performed on the Pt / G electrocatalyst of Example 1 using a PANALYTICAL X'PERT PRO instrument. The testing parameters used were Cu / Kα rays. The potential was 40kV, and the current was 15mA. The experimental results are as follows: Figure 3 As shown, Figure 3 The absence of diffraction peaks for Pt metal indicates that the mass content of Pt is less than the detection limit (1 wt%). The sample mass is 0.1 mg, therefore the Pt loading is ≤1 μg.
[0114] 2. Scanning electron microscope (SEM, Zeiss SUPRA 40) combined with energy dispersive spectroscopy (EDS)
[0115] The Pt / G electrocatalyst of Example 1 was analyzed using scanning electron microscopy combined with energy dispersive spectroscopy. The accelerating potential of the scanning electron microscope was 20 kV, and the energy dispersive spectroscopy used a silicon drift detector. Three sites (site 1, site 2, and site 3) were selected on the Pt / G electrocatalyst for calculation. The experimental results are as follows: Figure 4 As shown in Table 1, averaging the data from the three sites in Table 1 reveals that the mass fraction of Pt metal is approximately 0.5%. That is, in a 0.1 mg sample, according to formula m... Pt =0.1*1000*0.5%, so the Pt content is 0.5μg.
[0116] Table 1
[0117] Carbon mass fraction (%) 99.56 99.46 99.51 Platinum mass fraction (%) 0.44 0.54 0.49 total 100 100 100
[0118] The Pt / G electrocatalyst of Example 1 was analyzed using scanning electron microscopy combined with energy dispersive spectroscopy. A portion of the Pt / G sample was cut off, and its surface morphology was observed using scanning electron microscopy to obtain electron micrographs. Pt particles of approximately 10 nm (in bright areas) were observed to be uniformly supported on the graphite support. Figure 5 As shown.
[0119] 3. Catalytic hydrogen evolution performance analysis
[0120] 1) Preparation of electrolytes
[0121] Electrolyte for hydrogen evolution reaction: 0.5M H2SO4 aqueous solution; Electrolyte for oxygen reduction reaction: 0.1M KOH aqueous solution;
[0122] 2) Preparation of electrocatalysts
[0123] 1000 μg of commercial Pt / C (purchased from Alfaisa (China) Chemical Co., Ltd., product number 047381) was sonicated in 400 μL of solution to obtain a mixed solution. 20 μL of this mixed solution was then dropped onto a graphite rod (1 cm). 2 The value is 1000 / 400*(20 / 1)=50μg / cm. 2 A commercial electrocatalyst (Pt / C / G) was obtained, and subsequent tests were conducted on the commercial electrocatalyst, the electrocatalysts obtained in Examples 1-8 and Comparative Example 1.
[0124] 3) Use electrocatalysts to prepare hydrogen (hydrogen evolution reaction) and reduce oxygen (oxygen reduction reaction).
[0125] 3.1 Hydrogen evolution reaction: In the three-electrode system, hydrogen gas was first bubbled in 0.5M H2SO4 aqueous solution for 30 minutes. Then, a working potential of 0.1 to -0.3V (relative to the reversible hydrogen electrode) was applied to the working electrode using linear sweep voltammetry at a scan rate of 5mV / s, and the linear sweep voltammetry (LSV) polarization curve was recorded.
[0126] The Pd / G, Pt / G, PtPd / G from Example 1, the electrocatalysts from Examples 2-8, and Comparative Example 1 were subjected to hydrogen evolution reactions in 0.5 M H₂SO₄ aqueous solution, and linear sweep voltammetry (LSV) curves were obtained. Figure 6 It can be seen that at 10mA / cm 2 At the specified current density, the lower the hydrogen evolution overpotential, the better the hydrogen evolution performance. In other words, the electrocatalysts in Example 1 all exhibited superior performance, outperforming commercial electrocatalysts (Pt / C / G). Figure 7 It can be seen that the electrocatalyst of Example 2 is at 10 mA / cm 2 At the current density, the hydrogen evolution overpotential is 85 mV; Figure 8 It can be seen that the electrocatalyst in Example 3 has a performance of 10 mA / cm 2 At the current density, the hydrogen evolution overpotential is 93 mV; Figure 9 It can be seen that the electrocatalyst of Example 4 is at 10 mA / cm 2 At the current density, the hydrogen evolution overpotential is 85 mV; Figure 10 It can be seen that the electrocatalyst of Example 5 is at 10 mA / cm 2 At a current density of 10 mA / cm², the hydrogen evolution overpotential is 64 mV. The electrocatalyst of Example 6 exhibits this overpotential at 10 mA / cm². 2 At the current density, the hydrogen evolution overpotential is 57 mV; Figure 11 It can be seen that the electrocatalyst of Example 7 has a performance of 10 mA / cm 2 At a current density of 10 mA / cm², the hydrogen evolution overpotential is 60 mV; the electrocatalyst of Example 8 at 10 mA / cm²... 2 At a current density of 10 mA / cm², the hydrogen evolution overpotential is 57 mV; the electrocatalyst of Comparative Example 1 at 10 mA / cm²... 2 At the given current density, the hydrogen evolution overpotential is 137 mV.
[0127] 3.2 Hydrogen evolution reaction: In the three-electrode system, hydrogen gas was first bubbled in 0.5M H2SO4 aqueous solution for 30 minutes. Then, a working potential of 0.05 to 1.2 V (relative to the reversible hydrogen electrode) was applied to the working electrode using cyclic voltammetry at a scan rate of 50 mV / s, and the cyclic voltammetry (CV) polarization curve was recorded.
[0128] Cyclic voltammetry (CV) tests were performed on the Pt / G sample from Example 1 in a 0.5 M H₂SO₄ aqueous solution to obtain CV curves. The presence of oxidation peaks in the CV curves was determined, and the catalytic activity of the catalyst was evaluated by the area of the oxidation peaks. The results are as follows: Figure 12 As shown, the CV curves confirmed the presence of Pt, indicating that Pt was reduced onto the graphite rod and exhibited high catalytic activity.
[0129] 3.3 Oxygen reduction reaction: In the three-electrode system, oxygen was first bubbled in 0.1M KOH aqueous solution for 30 minutes. Then, a working potential of 1.17 to 0.17 V (relative to the reversible hydrogen electrode) was applied to the working electrode using linear sweep voltammetry (LSV) at a scan rate of 5 mV / s, and the LSV polarization curve was recorded.
[0130] The oxygen reduction performance of the Pt / G sample from Example 1 was tested in a 0.1M KOH aqueous solution to obtain the LSV curve, as shown below. Figure 13 As shown, the oxygen reduction reaction begins at 0.9V, and the current density increases as the potential decreases (becomes more negative), indicating that the electrocatalyst has oxygen reduction performance.
[0131] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," "some implementations," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0132] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for preparing an electrocatalyst, characterized in that, Includes the following steps: Using conductive carbon material as the working electrode, the working electrode, counter electrode, and reference electrode are fixed in an electrolyte. The working electrode is activated by maintaining its potential at -1 to -4V using a constant potential method to obtain the activated conductive carbon material. The activated conductive carbon material is then reacted with a noble metal salt solution to obtain an electrocatalyst. The activation time is 30 seconds to 3 minutes. The electrolyte is selected from organic electrolyte salts; the organic electrolyte salt is selected from organic lithium salts; and the organic lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethanesulfonyl)imide. The noble metal salt solution is selected from platinum salt solution and / or palladium salt solution.
2. The method for preparing the electrocatalyst according to claim 1, characterized in that, The potential of the working electrode is maintained at -2 to -2.4V in a constant potential manner.
3. The method for preparing the electrocatalyst according to claim 1, characterized in that, The reaction time is ≥5s.
4. The method for preparing the electrocatalyst according to claim 1, characterized in that, The conductive carbon material includes one or more of graphite, carbon nanotubes, carbon black, biochar, and activated carbon.
5. The method for preparing the electrocatalyst according to claim 1, characterized in that, Based on the volume of the electrolyte, the concentration of the organic electrolyte salt is 0.01~0.1 mol / L.
6. The method for preparing the electrocatalyst according to claim 1, characterized in that, Based on the volume of the precious metal salt solution, the concentration of the precious metal salt is 1 mmol / L to 1 mol / L.
7. An electrocatalyst prepared by the method of any one of claims 1-6.
Citation Information
Patent Citations
Carbon-loaded high-loading-capacity noble metal electrocatalyst as well as preparation method and application thereof
CN115513476A
A carbon nitride nanotube loaded with platinum and ruthenium nanoparticles electrode catalyst and its preparation
WO2008138269A1